Analisis kinerja pemerintah desa di Desa Malitu - Tunta, Jesisca; Mamuaya, Nova Ch.; Tangkau, Jaqueline E. M. (Riset Akuntansi dan Portofolio Investasi, 2024)
The aim of thus research is to determine the performance of the village government in carrying out village development and also in managing the allocation of village funds in Malitu village, whether it is in accordance with existing regulations and also in accordance with the indicators that must be carried out by the village government. The method used in this research is a descriptive method whit a qualitative approach. The results of the research show that the village government in carrying out its duties has followed the regulations and also the indicators or measurements used to see the performance of the village government, namely, productivity, service quality, responsiveness, responsibility, and accountability. So, it can be said that the performance of the Malitu village government is good. Likewise, for managing village fund allocations, the village government has used the implementation stage, supervision stage and also the accountability stage. So that realization of the village fund allocations is carried out well and in accordance whit the needs of the Malitu village community, even though there are obstacles faced in it, namely, the weather and also poor roads.